An Empirical Analysis of Factors Affecting the Housing Price in Shanghai - Wang, Yufang; Jiang, Yanqing (Asian Journal of Economic Modelling, 2016)
Being one of the most booming and prosperous cities of China, Shanghai is attracting more and more talents from all over the world. Although the development of real estate market contributes a lot to the economic take-off, the excessively high the housing price may cause big troubles. In order to find the main factors affecting the housing price in Shanghai, an econometric model is established and seven explanatory variables, per capita disposable income in Shanghai, land transaction price index, construction cost, urbanization rate, interest rate, CPI of residence and investment in real estate in Shanghai are taken into consideration based on the supply and demand theory. With the help of regression analysis, only interest rate is kicked out and the other six can all be a good explanatory variable for the housing price.